Analysis of the Effect of Lime Powder Substitution and Superplasticizer on the Compressive Strength of Mortar - Rizqian, Sahla Kayla; Salsabila, Dina; Nugraha, Prendy Prasetya; Roesdiana, Tira (PT FORMOSA CENDEKIA GLOBAL, 2025)
The increasing need for environmentally friendly construction materials encourages innovation in mortar development. This study analyzed the effect of lime powder substitution with superplasticizer on the compressive strength of mortar, using substitution variations of 0%, 5%, 10%, 15%, and 20% by weight of cement, and 2% superplasticizer addition. Tests were carried out at the age of 7, 14, 21, and 28 days with laboratory experimental methods according to SNI standards. The results showed that the combination of lime powder and superplasticizer significantly increased the compressive strength of mortar, with the optimum composition of 5% lime and 2% superplasticizer at 28 days reaching 16.29 MPa, an increase of 243.3% from the normal mortar of 4.74 MPa. The use of these additives improves mortar performance and supports cost efficiency and environmental sustainability.